Occupational dust exposure and the risk of laryngeal cancer in Turkey - Elci, Omur Cinar; Akpinar-Elci, Muge; Blair, Aaron; Dosemeci, Mustafa (Scandinavian Journal of Work, Environment & Health, 2002)
' ' OBJECTIVES ': 'A hospital-based case-referent study was conducted to identify occupational risk factors for laryngeal cancer. In a previous report an association was found between laryngeal cancer and occupations with potential dust exposure; a job-exposure matrix was developed to aid further evaluation of laryngeal cancer risks from five occupational dust exposures. ' ' METHODS ': 'Among 7631 cancer cases from the Okmeydani Hospital, Istanbul, between 1979 and 1984, 958 larynx cancer cases were identified among men. After exclusions, 940 laryngeal cancer cases and 1519 referents were available. A standardized questionnaire was used to obtain basic information on the patients. Seven-digit standard occupational and industrial codes were created to classify the job and industrial titles. A job-exposure matrix was developed for occupational dusts, including silica, asbestos, wood, cotton, and grain, and age-, smoking-, and alcohol-adjusted odds ratios (OR) and 95% confidence intervals (95% CI) were calculated to evaluate risks of laryngeal cancer. ' ' RESULTS ': 'An excess of laryngeal cancer occurred for workers potentially exposed to silica and cotton dust, particularly for supraglottic cancer (OR 1.8, 95% CI 1.3-2.3, for silica and OR 1.6, 95% CI 1.1-2.5, for cotton dust), and there was a significant dose-response relationship with silica exposure. No relationship was found between laryngeal cancer and asbestos, grain, or wood dust exposures. ' ' CONCLUSIONS ': 'Laryngeal cancer, especially supraglottic tumors, is associated with silica and cotton dust exposures in Turkey.
Keywords: case-control study; case-referent study; cotton; epidemiology; laryngeal cancer; larynx; occupational dust exposure; risk; silica; Turkey; work